Pulsed Doppler echocardiographic evaluation of neonatal circulatory changes. Issue 2 (February 1987) - Shiraishi, H; Yanagisawa, M
Abstract : Pulsed Doppler echocardiograms were obtained from 42 normal fullterm neonates at less than 12 hours (20 subjects), 4 days (20 subjects), and 33 days (12 subjects). The acceleration time of the flow velocity and ventricular systolic time intervals were measured on recordings obtained at the right and left ventricular outflow tract, and the patency of the ductus arteriosus was evaluated by the flow at the pulmonary end of the ductus. The flow velocity pattern of the right ventricular outflow tract changed from a triangular shape with a peak velocity in early systole in the younger age groups to a dome-like contour with a peak velocity in mid-systole; thus the ratio of mean acceleration time to right ventricular ejection time increased with age. The flow velocity pattern of the left ventricular outflow tract was triangular in all age groups, and the ratio of mean acceleration time to left ventricular ejection time showed no significant change with age. The right ventricular pre-ejection period shortened and the right ventricular ejection time lengthened with age; thus the ratio of mean right ventricular pre-ejection period to right ventricular ejection time decreased with age. The left ventricular systolic time intervals showed no significant change with age. The ductus arteriosus was patent in all subjects who were less than 12 hours old but was closed in the older neonates. Pulsed Doppler echocardiography is a valuable method of evaluating pulmonary vascular bed in the early neonatal period.